Imaging of enzyme activity using bio‐LSI system enables simultaneous immunosensing of different analytes in multiple specimens. Issue 6 (25th May 2016) - Hokuto, Toshiki; Yasukawa, Tomoyuki; Kunikata, Ryota; Suda, Atsushi; Inoue, Kumi Y.; Ino, Kosuke; Matsue, Tomokazu; Mizutani, Fumio
Abstract: Electrochemical imaging is an excellent technique to characterize an activity of biomaterials, such as enzymes and cells. Large scale integration‐based amperometric sensor (Bio‐LSI) has been developed for the simultaneous and continuous detection of the concentration distribution of redox species generated by reactions of biomolecules. In this study, the Bio‐LSI system was demonstrated to be applicable for simultaneous detection of different anaytes in multiple specimens. The multiple specimens containing human immunoglobulin G (hIgG) and mouse IgG (mIgG) were introduced into each channel of the upper substrate across the antibody lines for hIgG and mIgG on the lower substrate. Hydrogen peroxide generated by the enzyme reaction of glucose oxidase captured at intersections was simultaneously detected by 400 microelectrodes of Bio‐LSI chip. The oxidation current increased with increasing the concentrations of hIgG, which can be detected in the range of 0.01–1.0 µg mL ‐1 . Simultaneous detection of hIgG and mIgG in multiple specimens was achieved by using line pattern of both antibodies. Therefore, the presence of different target molecules in the multiple samples would be quantitatively and simultaneously visualized as a current image by the Bio‐LSI system. Abstract : Bio‐LSI systems can detect two analytes in different specimens simultaneously: Injection of specimens into microfluidic channels on the substrate with antibody lines gives rise to the pattern of immunocomplexes. Immunocomplexes labeled with enzyme can be detected as a current image to determine the different analytes in the multiple specimens. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB, visitwww.afob.org .